Analgesic Effect of Dayak Onion (Eleutherine americana (Aubl.) Merr.) on Mice (Mus musculus) by Hot Plate Test Method - Muhammad Hafizh; Danti Nur Indiastuti; Indri Safitri Mukono (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2021)
Introduction: Pain is an unpleasant experience that reduces a person's quality of life. Pain related complain can be treated by administering analgesic drugs. Several studies show that the availability of analgesics is still low, especially opioid analgesics. Dayak onion (Eleutherine americana (Aubl.) Merr.) are used by the Dayaks to relieve pain. Several empirical studies have shown that Dayak onion contain compounds including quercetin as a potential analgesic. This research aimed to investigate the potential analgesic effect of Dayak onion using hot plate method.Methods: The research was conducted experimentally on 36 BALB/c male mice which randomly divided into 6 different treatment groups of Dayak onion exctract, aspirin, codein and aquadest. Each group were thermally pain-induced for latency period measurement by the hot plate test method. Obtained data were processed using Analysis of Variance (ANOVA) followed by Dunnett test.Results: There was a difference in the latency period between the baseline response time and the response time after being treated in each group. ANOVA test results showed significant results (p<0.05) so that the resulting latency period was significant. Dunnett test results showed significant results (p<0.05) in negative control group. Based on these results, Dayak onion are proven to have an analgesic effect on heat stimulation.Conclusion: Dayak onion possess significant analgesic effect on thermally pain-induced mice. Dayak onion extract 90 mg/kg mouse produced better analgesic effects than aspirin 65 mg/kg mouse.